Unified Gas-Kinetic Wave-Particle Methods VI: Disperse Dilute Gas-Particle Multiphase Flow (Communications in Computational Physics, 2022)
A coupled gas-kinetic scheme (GKS) and unified gas-kinetic wave-particle(UGKWP) method for the disperse dilute gas-particle multiphase flow is proposed. Inthe two-phase flow, the gas phase is always in the hydrodynamic regime and is followed by GKS for the Navier-Stokes solution. The particle phase is solved by UGKWPin all regimes from particle trajectory crossing to the hydrodynamic wave interaction with the variation of particle’s Knudsen number. In the intensive particle collision regime, the UGKWP gives a hydrodynamic wave representation for the particlephase and the GKS-UGKWP for the two-phase flow reduces to the two-fluid Eulerian-Eulerian (EE) model. In the rarefied regime, the UGKWP tracks individual particle andthe GKS-UGKWP goes back to the Eulerian-Lagrangian (EL) formulation. In the transition regime for the solid particle, the GKS-UGKWP takes an optimal choice for thewave and particle decomposition for the solid particle phase and connects the EE andEL methods seamlessly. The GKS-UGKWP method will be tested in all flow regimeswith a large variation of Knudsen number for the solid particle transport and Stokesnumber for the two-phase interaction. It is confirmed that GKS-UGKWP is an efficientand accurate multiscale method for the gas-particle two-phase flow.
Keywords: Unified gas-kinetic wave-particle method; gas-kinetic scheme; disperse gas-particle two-phase flow.